2013
DOI: 10.1038/ncomms3979
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast viscous water flow through nanostrand-channelled graphene oxide membranes

Abstract: Pressure-driven ultrafiltration membranes are important in separation applications. Advanced filtration membranes with high permeance and enhanced rejection must be developed to meet rising worldwide demand. Here we report nanostrand-channelled graphene oxide ultrafiltration membranes with a network of nanochannels with a narrow size distribution (3-5 nm) and superior separation performance. This permeance offers a 10-fold enhancement without sacrificing the rejection rate compared with that of graphene oxide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
557
4
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 738 publications
(594 citation statements)
references
References 52 publications
23
557
4
4
Order By: Relevance
“…For example, by intercalating positively charged copper hydroxide nanostrands into GO laminates, followed by partially reducing and then dissolving the copper hydroxide nanostrands, the resulting nanostrand-channeled GO membranes offer a 10-fold enhancement in permeance without sacrificing the rejection rate of organic molecules compared with pristine GO membranes. 30 By intercalating carbon nanotubes into GO layers, the water permeance can be enhanced significantly compared with pure GO membranes, whereas the rejection rates toward large organic molecules are still high. 31,32 Recently, we intercalated monolayer titania-NS into GO laminates, followed by UV-induced photocatalytic reduction, and found that as-prepared reduced GO/titania hybrid membranes showed excellent ion rejection performance while the high water permeance of GO membranes could be preserved.…”
Section: Introductionmentioning
confidence: 99%
“…For example, by intercalating positively charged copper hydroxide nanostrands into GO laminates, followed by partially reducing and then dissolving the copper hydroxide nanostrands, the resulting nanostrand-channeled GO membranes offer a 10-fold enhancement in permeance without sacrificing the rejection rate of organic molecules compared with pristine GO membranes. 30 By intercalating carbon nanotubes into GO layers, the water permeance can be enhanced significantly compared with pure GO membranes, whereas the rejection rates toward large organic molecules are still high. 31,32 Recently, we intercalated monolayer titania-NS into GO laminates, followed by UV-induced photocatalytic reduction, and found that as-prepared reduced GO/titania hybrid membranes showed excellent ion rejection performance while the high water permeance of GO membranes could be preserved.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, such an approach does not compromise the rejection efficiency of the membrane for pollutants such as organic dyes. 69,70 In practice, challenges and solutions. Although numerous studies have shown the applicability of this class of membranes for water desalination, in particular as NF membranes, many studies in the literature have addressed current challenges.…”
Section: Multilayer Graphene Desalination Membranesmentioning
confidence: 99%
“…In contrast, suitable thin membrane filters-such as those fabricated from thin-film SiN x -allow for much higher flow rates. 13,[47][48][49][50]52,69,232,249,307,320,321 When formed using nanofabrication-compatible materials, these porous thinfilm platforms can be readily integrated into devices and moreover modified to generate functions beyond filtering. Nanopore filters coated with suitable coinage metal films can combine filtering with surface-enhanced Raman spectroscopy (SERS).…”
Section: -319mentioning
confidence: 99%